Behavioural analysis of multi-year satellite telemetry data provides insight into narwhal (Monodon monoceros) winter prey selection in Baffin Bay - Claire A. Hornby; Ron R. Togunov; Brett T. McClintock; Cortney A. Watt (PLoS ONE, 2025)
Narwhals (Monodon monoceros) are deep-diving Arctic cetaceans that migrate seasonally between summering and wintering grounds. The Baffin Bay population overwinters in southern Baffin Bay and Davis Strait, where they are known to forage on high-energy benthic prey. Studying narwhal winter behaviour and prey preference has been challenged by their remote distribution and limited lifespan of satellite tags deployed in summer, restricting data on their habitat use and foraging strategies. Since prey consumption is thought to peak in the winter, understanding narwhal diet plasticity in a rapidly changing environment like Baffin Bay is critical. This study developed unique methods to examine four years of irregular satellite telemetry data from 22 narwhals tagged in their summering grounds. Locations and recorded diving data from the overwintering area were isolated, and a hidden Markov model was used to define three behaviours (“surface”, “pelagic”, and “deep-water” diving). We further examined the effects of five covariates on these behaviours to provide insight into the spatial patterns of narwhal winter prey preference. Narwhal behaviours were dominated by diving, with 37% of their time spent in pelagic waters and 40% in deep-water, while only 22% of their time was spent in surface related behaviours. Deep-water behaviours increased later in the day and into the winter season and occurred frequently in the center trough of Baffin Bay before (66°- 69°) and across Davis Strait (65° - 67°). In contrast, pelagic behaviours declined as the winter season progressed and occurred earlier in the day. Narwhals occupying the northern overwintering area exhibited more pelagic behaviours, despite it being deeper, suggesting different foraging strategies across their winter range. Our study identified behaviours suggestive of a variable winter diet and provided insight on the spatial nature of these behaviours across the winter season. The methods developed in this study present new opportunities for analysing lower resolution satellite tracking data. With advancements in bio-logging technology and remote field methods, the ability to successfully document changes in winter space use and fine-scale foraging behaviours may be possible for narwhal in the future.